Demonstration of pressure reduction in a new proof of concept spine board. Issue 6 (2nd November 2021) - Sun, Helen; Wilson, James; Roach, Mary Joan; Hefzy, Mohamed Samir; Nemunaitis, Greg
ABSTRACT: Pressure injuries are a significant problem following spinal cord injury (SCI). High interface pressures while lying on a spine board during emergency transport appear to play a major role in their formation. The aim of the present study was to assess the interface pressures and sensing area between the body and the standard spine board (SSB) and a proof of concept spine board prototype ( P -5). Twenty-one able-bodied subjects were assessed on each board. Interface pressures and sensing area were recorded every minute over 15 min. The mean peak pressure was higher on the SSB at the head, scapulothoracic (S-T), sacroiliac (S-I), and heels (227.6 mmHg, 148.9 mmHg, 360.3 mmHg, and 179.3 mmHg) compared to P -5 (51.9 mmHg, 60.1 mmHg, 66.8 mmHg, and 60.2 mmHg). The peak pressure index (PPI) at the head, S-T and S-I was higher on the SSB (100.2 mmHg, 101.6 mmHg, and 270.6 mmHg) compared to P -5 (41.6 mmHg, 51.9 mmHg and 58.7 mmHg). An analysis using pairwise comparisons for repeated measures showed that interface pressures ( p < .05) and PPI ( p < .001) were reduced at all locations. Modifications of a spine board incorporated in P -5 can dramatically reduce interface pressures and reduce pressure injury formation.